2010
DOI: 10.2119/molmed.2010.00023
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated mTOR Signaling and Enhanced Autophagy in Adipocytes from Obese Patients with Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is strongly linked to obesity and an adipose tissue unresponsive to insulin. The insulin resistance is due to defective insulin signaling, but details remain largely unknown. We examined insulin signaling in adipocytes from T2D patients, and contrary to findings in animal studies, we observed attenuation of insulin activation of mammalian target of rapamycin (mTOR) in complex with raptor (mTORC1). As a consequence, mTORC1 downstream effects were also affected in T2D: feedback signaling by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(131 citation statements)
references
References 70 publications
6
121
0
Order By: Relevance
“…Given that FoxO1 is activated by insulin resistance 20,46,47 , the FoxO1-autophagy-FSP27 axis may promote LD and adipocyte expansion in obese insulin resistant subjects, thereby casting light on the pathological relevance of augmented autophagy in adipose tissues from obese subjects. [7][8][9][10][11][12] To the best of our knowledge, this is also the first study investigating the role of FoxO1 in the regulation of adipose autophagy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Given that FoxO1 is activated by insulin resistance 20,46,47 , the FoxO1-autophagy-FSP27 axis may promote LD and adipocyte expansion in obese insulin resistant subjects, thereby casting light on the pathological relevance of augmented autophagy in adipose tissues from obese subjects. [7][8][9][10][11][12] To the best of our knowledge, this is also the first study investigating the role of FoxO1 in the regulation of adipose autophagy.…”
Section: Discussionmentioning
confidence: 85%
“…6 Recent studies show that increased adiposity is associated with augmented autophagy in the adipose tissue from obese and type 2 diabetic humans and rodents. [7][8][9][10][11][12][13][14] Genetic suppression of autophagy by targeting autophagy related 5 (Atg5) or Atg7 in adipose tissue reduces adipocyte size, increases energy expenditure, and protects mice against diet-induced obesity. [15][16][17] Moreover, deletion of Atg5 suppresses adipogenesis (de novo formation of adipocytes).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms of this defect could be diverse. Since obesity is characterized with enhanced intracellular lipid accumulation (Ost et al 2010), the role of progranulin with sustained lipogenesis might be much more complicated than expected. It is plausible that chronic lipid overloading, which might impair insulin signaling and insulin-stimulated glucose uptake, might be one of the triggers in metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent studies have shown that autophagy is upregulated in adipocytes from diabetic mice or obese patients. [3][4][5][6][7][8] Adipose-specific deletion of a key autophagy gene, such as atg5 or atg7, led to lean mice and improved insulin sensitivity and glucose homeostasis in the whole body of mice. 6,7,9 One of the key features with the mouse models was a reduction in the white adipose tissue (WAT) mass, and an increase in the brown adipose tissue (BAT) mass.…”
Section: Introductionmentioning
confidence: 99%